HASIL BELAJAR SISWA BERDASARKAN INTENSITAS KEGIATAN BRAIN GYM PADA PEMBELAJARAN MATEMATIKA - Agustina, Winda; Wahyuni, Sri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2018)
Learning is an effort to improve the self quality and the education quality. Observations show that students have difficulty concentrate on learning in full seen by the students themselves with their activities. Brain Gym activities to learning can help students' learning readiness factors. The purpose of this study was to find out how student learning outcomes with brain gym activities based on low intensity and high intensity in mathematics learning in class VIII of SMP Negeri 9 Banjarbaru. In addition, also to find out the differences in student learning outcomes based on the intensity of brain gym activities in mathematics learning. This study used a quantitative approach and uses a type of experimental research. The results showed that the learning outcomes of students using brain gym with low intensity were in sufficient qualification, high intensity brain gym was in good qualification, and there were differences in student learning outcomes based on the intensity of Brain Gym use in mathematics learning in class VIII of SMP Negeri 9 Banjarbaru.Â Keywords:brain gym, learning outcome